2010
DOI: 10.1038/labinvest.2010.145
|View full text |Cite
|
Sign up to set email alerts
|

Gene delivery of TGF-β1 induces arthrofibrosis and chondrometaplasia of synovium in vivo

Abstract: To understand the cellular and molecular events contributing to arthrofibrosis, we used an adenovirus to deliver and overexpress transforming growth factor-beta 1 (TGF-β1) cDNA (Ad.TGF-β1) in the knee joints of immunocompromised rats. Following delivery, animals were killed periodically, and joint tissues were examined macroscopically and histologically. PCR-array was used to assay alterations in expression patterns of extracellular matrix (ECM)-associated genes. By days 5 and 10, TGF-β1 induced an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 67 publications
5
72
0
2
Order By: Relevance
“…Our study indicated an important role of synovial cells in the process of neocartilage metaplasia that was observed primarily at the transition zone where the synovium connects to the meniscus or articular cartilage, mimicking the osteophyte formation observed in OA. Watson and colleagues (28) observed similar ectopic chondrogenesis and reported that gene delivery of transforming growth factor ␤1 induced massive proliferation of synovial fibroblasts and chondrometaplasia of synovium in vivo (28).…”
Section: Discussionmentioning
confidence: 78%
“…Our study indicated an important role of synovial cells in the process of neocartilage metaplasia that was observed primarily at the transition zone where the synovium connects to the meniscus or articular cartilage, mimicking the osteophyte formation observed in OA. Watson and colleagues (28) observed similar ectopic chondrogenesis and reported that gene delivery of transforming growth factor ␤1 induced massive proliferation of synovial fibroblasts and chondrometaplasia of synovium in vivo (28).…”
Section: Discussionmentioning
confidence: 78%
“…Specifically, the direct gene transfer of TGFB1 to synovial lining cells by intraarticular injection of adenoviral vectors resulted in fibrosis and ectopic chondrogenesis in native and arthritic leporine knee joints 24 , as well as in native knee joints of immunocompromised rats 25 . Using a method of indirect in vivo gene therapy, Gelse et al transplanted perichondrial mesenchymal stromal cells after ex vivo transduction with adenoviral vectors carrying BMP2 genes into chondral defects of rat knees 26 .…”
Section: Bmp-2 and Ihh For Articular Cartilage Repairmentioning
confidence: 99%
“…The exact etiology is unknown, but proposed causes include a genetic predisposition to scar formation, an aberrant inflammatory response to an injury or surgery, or simply prolonged joint immobilization. 12,13 Arthrofibrosis is seen most commonly in children after treatment of tibial eminence fractures. Patel et al 9 retrospectively reviewed 40 patients with tibial eminence fractures and concluded that those who started range-of-motion exercises .4 weeks after injury required more time to return to full activity and were 12 times more likely to develop arthrofibrosis.…”
Section: Arthrofibrosismentioning
confidence: 99%